PENGARUH PENGETAHUAN PRODUK DAN PROMOSI PENJUALAN TERHADAP NIAT BELI PELANGGAN TELEPON RUMAH PADA LAYANAN SPEEDY PRE WIRED - SYAMSU, ADITYA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: This research is focused on speedy pre wired as fixed line service, where many customers are still reluctant to migrate to prepaid electricity. This research aims to analyze and discuss the influence of product knowledge and sales promotion on purchase intention. The research is conclusive research. The population in this research is fixed line customers who has got speedy pre wired service in GKB, Gresik. Samples were taken 84 Telkom’s customers with a simple random sampling technique. Measuring instrument was a questionnaire and to test the hypothesis used multiple linear regression analysis tool. The results show product knowledge and sales promotion all have a significantly positive influence on purchase intention. Further research could examine the different dimensions of product knowledge and sales promotion on consumer purchase intention. Keywords: product knowledge, sales promotion, and purchase intention